Mitigating losses: how scientific organisations can help address the impact of the COVID-19 pandemic on early-career researchers - Sandra López-Vergès (Springer Nature, 2021)
Scientific collaborations among nations to address common problems and to build international partnerships as part of science diplomacy is a well-established notion. The international flow of people and ideas has played an important role in the advancement of the ‘Sciences’ and the current pandemic scenario has drawn attention towards the genuine need for a stronger role of science diplomacy, science advice and science communication. In dealing with the COVID-19 pandemic, visible interactions across science, policy, science communication to the public and diplomacy worldwide have promptly emerged. These interactions have benefited primarily the disciplines of knowledge that are directly informing the pandemic response, while other scientific fields have been relegated. The effects of the COVID-19 pandemic on scientists of all disciplines and from all world regions are discussed here, with a focus on early-career researchers (ECRs), as a vulnerable population in the research system. Young academies and ECR-driven organisations could suggest ECR-powered solutions and actions that could have the potential to mitigate these effects on ECRs working on disciplines not related to the pandemic response. In relation with governments and other scientific organisations, they can have an impact on strengthening and creating fairer scientific systems for ECRs at the national, regional, and global level.